2021
DOI: 10.2147/rmhp.s293471
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Health System Response to the COVID-19 Pandemic on Chronic Disease Management: A Narrative Review

Abstract: Background Individuals with chronic conditions require ongoing disease management to reduce risks of adverse health outcomes. During the COVID-19 pandemic, health care for non-COVID-19 cases was affected due to the reallocation of resources towards urgent care for COVID-19 patients, resulting in inadequate ongoing care for chronic conditions. Methods A keyword search was conducted in PubMed, Google Scholar, Science Direct, and Scopus for English language articles publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
170
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(181 citation statements)
references
References 99 publications
9
170
0
2
Order By: Relevance
“…In addition to this, some studies have indicated that health care for chronic illness during COVID-19 outbreaks has been disrupted, which can be a constant source of stress. 11 , 29 On the other hand, this finding was lower than in a study conducted in India among patients undergoing hemodialysis, where the level of perceived stress was 97%. 30 The possible reason for this is that patients receiving hemodialysis may be threatened with more potential losses and changes in lifestyle compared with people with other chronic diseases.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…In addition to this, some studies have indicated that health care for chronic illness during COVID-19 outbreaks has been disrupted, which can be a constant source of stress. 11 , 29 On the other hand, this finding was lower than in a study conducted in India among patients undergoing hemodialysis, where the level of perceived stress was 97%. 30 The possible reason for this is that patients receiving hemodialysis may be threatened with more potential losses and changes in lifestyle compared with people with other chronic diseases.…”
Section: Discussionmentioning
confidence: 72%
“…16 Moreover, disruptions to ongoing health-care services for chronic disease patients will further worsen their health and perceived stress as a result of the shifting of health services to urgent COVID-19 patients. 11 Coping strategies refer to behavioral and cognitive efforts that help to reduce the influence of a stressful condition, 17 and are used when its demands exceed individual resources. 18 The relationship between stress and coping strategies has been a topic of previous studies, 19,20 because in critical situations stress affects many people, but individual responses vary according to their coping strategies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increase in the use of telemedicine is expected to impact healthcare access quality, care costs, and education. Telemedicine technologies applied to home care have the potential to impact to present cardiac care models and explore the communication among experts, leading to have high-quality, more efficient, and less expensive care [ 42 , 43 ]. These models can function as a platform to provide primary care and management of critical care patients in a sophisticated manner [ 39 ].…”
Section: Resultsmentioning
confidence: 99%